2013
DOI: 10.1176/appi.ajp.2013.12060858
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Characteristics of Homicide Defendants

Abstract: Rates of axis I disorders were lower than reported in previous studies. Few homicide defendants were in psychiatric treatment at the time of the crime, suggesting limited opportunities for prevention by mental health providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…They concluded that most perpetrators of homicide were neither acutely ill nor under mental health care at the time of the offense. Their findings echoed results from the Martone et al (2013) study in the United States, which, in an unselected sample of defendants charged with homicide between 2001 and 2005, found that 58% had at least one Axis I or II diagnosis (47% with substance misuse) and 37% had prior psychiatric contact. Despite these high lifetime prevalence rates, only 8% of those with Axis I disorders were receiving treatment in the 3 months prior to the homicide.…”
Section: Mental Disorder and Homicidementioning
confidence: 54%
“…They concluded that most perpetrators of homicide were neither acutely ill nor under mental health care at the time of the offense. Their findings echoed results from the Martone et al (2013) study in the United States, which, in an unselected sample of defendants charged with homicide between 2001 and 2005, found that 58% had at least one Axis I or II diagnosis (47% with substance misuse) and 37% had prior psychiatric contact. Despite these high lifetime prevalence rates, only 8% of those with Axis I disorders were receiving treatment in the 3 months prior to the homicide.…”
Section: Mental Disorder and Homicidementioning
confidence: 54%
“…Homicide is a major public health and social concern in the United States (Cooper and Smith 2011;Martone et al 2013;Matejkowski et al 2008). Approximately 15,000 homicides took place every year over the past decade (Martone et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 15,000 homicides took place every year over the past decade (Martone et al 2013). Studies have found higher rates of psychiatric disorders in homicide off enders than in the general population (Martone et al 2013;Matejkowski et al 2008;C ô t é and Hodgins 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to contact by email all but one [19] of the authors of epidemiological studies of homicide in schizophrenia published after 1981, but we were only able to contact the authors of one of the 8 studies published between published between 1960 and 1981. The authors of two studies were not able to provide further data because homicide recidivism was not part of their research design [27,32]. The authors of 10 studies provided previously unreported data about homicide recidivism.…”
Section: Resultsmentioning
confidence: 99%